MENINGKATKAN PEMAHAMAN MEMBACA TEKS BAHASA INGGRIS SISWA MELALUI PELATIHAN INFLECTIONAL MORPHEMES BERBASIS VIDEO PEMBELAJARAN (Jurnal AbdiMas Nusa Mandiri, 2026)
This Community Service Program was implemented at Madrasah Aliyah Diniyah Puteri Pekanbaru, located at Jalan KH. Ahmad Dahlan No. 100, Kampung Melayu, Kec. Sukajadi. This program aims to provide training to MA students on the use of video-based inflectional morphemes.The program was motivated by the problem of students who had difficulty understanding and using inflectional morphemes, a linguistic skill that is crucial for improving the accuracy of English reading comprehension. In the context of English as a foreign language (EFL) education in Indonesia, limited exposure to authentic English usage and insufficient emphasis on morphology instruction often hinder students' fluency and accuracy in reading. Mastery of morphological structures, particularly inflectional morphemes, is a crucial foundation for interpreting grammatical meaning and improving overall communication skills. The training participants were 29 Grade 11 science students with low initial comprehension scores based on pre-test results. The training was conducted using discussion and demonstration methods supported by instructional videos containing explanations, examples, and applications of inflectional morphemes in sentence contexts. The activity was carried out in three stages: observation, implementation, and evaluation through pre-tests and post-tests. The results showed a significant increase in the average score, from 45.5 before the training to 67.7 after the training. In addition to academic improvement, this program also encouraged student engagement, increased confidence in using English, and fostered active participation in class discussions. These findings confirm that integrating educational videos into English language instruction can effectively enhance understanding of morphological concepts and their application in reading, writing, and real-world communication.
Keywords: english text book; inflexional morphemes; instructional video